Bioavailability of ellagitannins from cambuci (Campomanesia Phaea Berg) in healthy and obese subjects - Silva, Rafaela Rossi e (2022)
Cambuci (Campomanesia phaea Berg) is a native fruit of the Atlantic Coastal Forest, belonging to the Myrtaceae family, rich in ellagitannins (ET), proanthocyanidins and other bioactive phenolic compounds (BPCs) related to beneficial effects to human health, such as systemic inflammation and attenuation of insulin resistance. Evidence indicates that the beneficial effects of some BPCs, such as ellagitannins, are associated to their chronic intake and the action of the metabolites produced. Urolithins are the main metabolites produced after consumption from a rich source of ellagitannins. According to the metabolite produced, subjects can be classified into metabotypes (A, B e 0). However, nothing is known about the uptake and metabolism of BPC from cambuci. Thus, the objectives of this study were the physical-chemical characterization of cambuci pulp, identification of BPC profile and the determination of their bioavailability in healthy and overweight/obese subjects. Therefore, subjects (n = 28, being 15 healthy and 13 overweight/obese) consumed cambuci juice, and their respective urines 24 hours after drinking were collected to identify the metabolites of ellagitannins. Cambuci presented high acidity, with pH values of ~ 2.3 and titratable acidity of ~ 1.9 g citric acid equivalents/100 g fresh weight (FW), and solids content of ~7.5 ° Brix, not being characterized as a very sweet fruit. The total phenolic content was ~ 780 mg gallic acid/100 mL juice. The total amount of flavan-3-ols found in the fruit was 45.45 g/kg dry weight (DW) and the main monomers identified were gallocatechin (22.25 g/kg DW) and epigallocatechin gallate (16.48 g/kg DW). The degree of polymerization of flavan3-ol was 32.78, indicating a high intensity of astringency and low bioavailability. Through LC-MS, 26 BPCs were identified, most of them being derived from ellagitannins, and among those identified, telemagrandin II and, pedunculagin. The total ellagic acid content found was ~6.2 mg/g DW, demonstrating that cambuci is a fruit rich in ellagic acid and its derivatives. The 28 volunteers who consumed cambuci juice for the bioavailability assessment were classified, for the first time, into metabotypes according to the type of urolithin produced. Metabotype A was the most prevalent (64.3%), followed by metabotype B (17.9%) and 0 (17.9%). When analyzed according to nutritional status, metabotype A was prevalent in both groups. In conclusion, the BCP profile of cambuci stands out for the presence of ET, such as telemagrandin II and pedunculagin. Due to the high degree of polymerization, no proanthocyanidin metabolites were observed. Metabotype A was the most prevalent in this study population, and nutritional status may not be a determining factor in the type of urolithin produced.